A Bibliometric Analysis of CEO Narcissism in Accounting Research - Arni Karina; Muhammad Nur; Molina; Kumba Digdowiseiso; Azwadi Ali (CV ODIS, 2023)
The progress of a company cannot be separated from the role of the Chief Executive Officer or CEO. The CEO is the party who occupies the highest position in the company and has a big influence on the decisions taken by a company. To assess the quality of a CEO, you can use the CEO's level of narcissism. CEO narcissism consists of positive and negative narcissism. Positive narcissism is indicated by optimism, while negative narcissism is indicated by arrogance. Therefore, research on CEO narcissism is needed in accounting research, considering that accounting plays a role in showing financial transactions in the company. The method used is bibliometric analysis with VOSviewer and perish or publish. Based on research, it is known that